Kontribusi Instrumen Moneter Syariah Terhadap Pengendalian Inflasi di Indonesia - Anya Regista Cahyani; Difa Ardini; Salsabilah Nurhidayah (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Inflation is a significant economic challenge in Indonesia, affecting price stability and people's purchasing power. In a sharia economic perspective, inflation is not only seen as an economic phenomenon, but also involves moral and social aspects. This article discusses the role of sharia monetary instruments in controlling inflation in Indonesia, highlighting the principles of fairness and transparency. Instruments such as Bank Indonesia Sharia Certificates (SBIS), Bank Indonesia Sharia Savings Facilities (FASBIS), and Sharia Open Market Operations (OPT) have been implemented to regulate the amount of money in circulation and maintain economic stability. Although their contribution to controlling inflation is still limited, the potential of sharia instruments can be strengthened through increasing market understanding, education and collaboration between the government, Bank Indonesia and sharia financial institutions. With more optimal implementation, sharia monetary instruments can create a stable, fair and sustainable economic system for the Indonesian people.